The Problem of Marriage Dispensation Between Theory and Practice - Nabil Fikri Palasenda (Mawaddah: Jurnal Hukum Keluarga Islam, 2025)
The dynamics of marriage law in Indonesia show the great influence of political power, which is shaped by religious interpretations that allow child marriage. This religious view is often the basis for legal decision-making, which legitimizes child marriage in the eyes of society. Although the Marriage Law has been revised, the existence of the marriage dispensation article creates a loophole that allows child marriage to continue to occur, with many judges approving dispensation applications due to the influence of legal norms and religious beliefs. This study uses a type of qualitative research with literature analysis and literature study methods. The type of data in this research will be collected from a variety of sources, including books, scientific journals, and other related documents. Through a comprehensive literature review and analysis of various journal articles, books, and other relevant sources, the purpose of this study is to examine the meaning of what a marriage dispensation is and how the application process is, why theories and practices regarding its regulations still have problems in its implementation and how solutions can be offered from it. The results of the study show that the Revision of the Marriage Law in Indonesia is not enough to overcome child marriage, because there is a gap in the dispensation article that still allows child marriage to occur and does not even clearly regulate the practice.